TUC Demonstration, March 1980 (London, 1980)
1980 1980-95 "TUC Demonstration, March 1980" [BW0225], 1980, Trades Union Congress As part of its Campaign for Economic and Social Advance, the TUC organised a National Demonstration in London from Hyde Park to Trafalgar Square on 9 March 1980, followed by a Day of Action on 14 May, to show the strength of opposition to the Conservative Government's economic and social policies and also to the Employment Bill. This photo shows two men on the march, wearing stickers supporting the national steel strike which was in progress at the same time.